Women have worse cognitive, functional, and psychiatric outcomes at hospital discharge after cardiac arrest. (April 2018) - Agarwal, Sachin; Presciutti, Alex; Verma, Jayati; Pavol, Marykay A.; Anbarasan, Deepti; Brodie, Daniel; Rabbani, Leroy E.; Roh, David J.; Park, Soojin; Claassen, Jan; Stern, Yaakov
Abstract: Aim: To examine gender differences among cardiac arrest (CA) survivors' cognitive, functional, and psychiatric outcomes at discharge. Methods: This is a prospective, observational cohort of 187 CA patients admitted to Columbia University Medical Center, considered for Targeted Temperature Management (TTM), and survived to hospital discharge between September 2015 and July 2017. Patients with sufficient mental status at hospital discharge to engage in the Repeatable Battery for Neuropsychological Status (RBANS), Modified Lawton Physical Self-Maintenance Scale (M-PSMS), Cerebral Performance Category Scale (CPC), Center for Epidemiological Studies Depression Scale (CES-D), and Post-Traumatic Stress Disorder Checklist – Civilian Version (PCL-C) were included. Fisher's exact, Wilcoxon Rank Sum, and regression analysis were utilized. Results: 80 patients (38% women, 44% white, mean age 53 ± 17 years) were included. No significant gender differences were found for age, race, Charlson Comorbidity Index, premorbid CPC or psychiatric diagnoses, arrest related variables, discharge CPC, or PCL-C scores. Women had significantly worse RBANS (64.9 vs 74.8, p = .01), M-PSMS (13.6 vs 10.6, p = .02), and CES-D (22.8 vs 14.3, p = .02) scores. These significant differences were maintained in multivariate models after adjusting for age, initial rhythm, time to return of spontaneous circulation, and TTM. Conclusions: Women have worse cognitive, functional, and psychiatric outcomes at hospital discharge after cardiac arrest than men. Identifying factors contributing to these differences is of great importance in cardiac arrest outcomes research.